The revival of The Bali Zoo marketing strategy post-covid-19 pandemic through digital marketin - Mega Wulansari; Sri Wisudawati (Universitas Pendidikan Nasional, 2021)
Bali Zoo Park is one of the tourist spots affected by the coronavirus. The aim of this research was to examine how to activate or revive programs and activities at Bali Zoo Park through marketing and innovation strategies in dealing with the new normal post-COVID-19 pandemic order. This study used qualitative data and the data was collected through passive participation observation techniques, semi-structured interviews, and documentation. Informants in this study were selected by using a purposive sampling technique which consists of the marketing manager, marketing staff, and consumers. The findings of this research suggested that Bali Zoo Park has implemented a marketing innovation strategy from conventional to digital. Digital marketing opens opportunities for Bali Zoo Park to boost sales during the new normal. The role of digital marketing is very influential in improving marketing performance in promoting its products with relevant and timely consumer reach with digital electronic devices.